Kartu Prakerja Program and Youth Employment: Gender-Specific Outcomes in Indonesia - Anggara, Rizki Tri (Economics and Finance in Indonesia, 2024)
The Kartu Prakerja Program is a form of the active labor market policy in Indonesia, serving as a significant initiative to enhance competencies and job opportunities, including for vulnerable groups such as the young and female labor force. This study aims to analyze the program’s impact on youth employment, with a focus on gender differences. Using Propensity Score Matching (PSM), the results show a significant positive effect on employment probability, particularly for women. The findings suggest that skills training and financial incentives play a crucial role in enhancing employability. The study recommends expanding program access to vulnerable groups and continuously assessing its effectiveness.